Strategi Peningkatan Sustainable Supply Chain Performance pada Perusahaan Remanufaktur Melalui Sustainable Value Stream Mapping (SUS-VSM) - Ade Meutia Ulfah; Agus Mansur (SENTRI: Jurnal Riset Ilmiah, 2026)
: In the era of globalization and rapid technological development, companies are required to remain competitive while addressing the social and environmental impacts of their business activities. This condition has encouraged the adoption of Sustainable Supply Chain Management (SSCM), which emphasizes not only efficiency and profitability but also sustainability. Remanufacturing, as part of the circular economy, offers a strategic solution by reducing waste, conserving resources, and preserving product value. This study aims to evaluate the SSCM performance of PT Komatsu Remanufacturing Asia using Sustainable Value Stream Mapping (Sus-VSM) integrated with the Analytical Hierarchy Process (AHP). A field study approach was employed through direct observation, interviews, and the collection of primary and secondary data. Sustainability metrics were developed based on a literature review and validated using AHP, supported by consistency, validity, and reliability testing. The results indicate that the company’s SSCM performance is classified as Moderately Good, with a sustainability index score of 77. Environmental and social dimensions demonstrate relatively strong performance, while the economic dimension requires further improvement, particularly in lead time reduction, Overall Equipment Effectiveness (OEE), water-use efficiency, and solid waste management. These findings highlight the importance of Sus-VSM as a comprehensive evaluation tool to support continuous sustainability improvement in remanufacturing supply chains.